1990
DOI: 10.4049/jimmunol.144.4.1382
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of antibody-dependent cytotoxicity with a chimeric anti-GD2 antibody.

Abstract: A mouse/human chimeric antibody (ch14.18) was developed that reacts with the disialoganglioside GD2 on the surface of tumor cells of neuroectodermal origin. ch14.18 has the constant regions of a human IgG1 antibody and was expressed in a murine hybridoma. This antibody was produced in tissue culture at concentrations up to 180 mg/liter of spent culture fluid. ch14.18 was characterized and compared to 14.G2a, a murine mAb against GD2 of IgG2a isotype derived from the same parental hybridoma as ch14.18. Scatchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Although the chemotherapy backbone was identical and the major prognostic factors of our patient populations were comparable with those of ANBL02P1, 14 ANBL0532, 15 and ANBL12P1 25 (Appendix Table A1), several other differences in therapy might have contributed to the excellent NB2012 response rates. For example, GM-CSF was used during induction chemoimmunotherapy, rather than filgrastim, both for its ability to enhance ADCC 33,34 and for primary prophylaxis of febrile neutropenia. 35 Additionally, low-dose IL-2 was used for its ability to enhance ADCC.…”
Section: Discussionmentioning
confidence: 99%
“…Although the chemotherapy backbone was identical and the major prognostic factors of our patient populations were comparable with those of ANBL02P1, 14 ANBL0532, 15 and ANBL12P1 25 (Appendix Table A1), several other differences in therapy might have contributed to the excellent NB2012 response rates. For example, GM-CSF was used during induction chemoimmunotherapy, rather than filgrastim, both for its ability to enhance ADCC 33,34 and for primary prophylaxis of febrile neutropenia. 35 Additionally, low-dose IL-2 was used for its ability to enhance ADCC.…”
Section: Discussionmentioning
confidence: 99%
“…Both the value‐adding ability and invasive activity of GD2‐transfected cells were significantly enhanced, and cell growth was significantly inhibited by the addition of monoclonal antibody 99 . Mujoo et al and Mueller et al demonstrated that mouse anti‐GD2 monoclonal antibodies 14.G2a and ch14.18 have a high affinity for GD2‐positive neuroblastoma cells and can effectively direct the antibody‐dependent cell‐mediated cytotoxicity 104,105 . The data suggest that the monoclonal antibody 14.18 binds strongly to SCLC cell lines and mediates tumor burn killing both in vivo and in vitro 106 .…”
Section: Disialogangliosidementioning
confidence: 99%
“…We first validated that GD2 expression could be observed and quantified on neuroblastoma patient-derived cell lines (PDCLs) using dinutuximab directly conjugated to Alexa Fluor 647. The specificity of ch14.18 (dinutuximab) for GD2 has been previously validated [44][45][46]. We characterized dinutuximab binding across a panel of ten patientderived neuroblastoma PDCLs that represented a variety of disease stages and tumor types.…”
Section: Evaluation Of Surface Markers On Neuroblastoma Cell Linesmentioning
confidence: 99%